LEARNING OUTCOME INCREASE OF TWO-DIMENSIONAL FIGURE CIRCUMFERENCE AND WIDE THROUGH TOUCH MEDIA - Hartati, Siti; Ruminiati, Ruminiati; Yulianti, Lia; Atweh, Bill (Journal of K6, Education and Management, 2018)
This study aims to improve the learning outcome increase of two-dimensional figure circumference and wide of the fourth-grade students through touch media. This study is a classroom action research and conducted in grade IV D at Sabilal Muhtadin Islamic Elementary School, Banjarmasin academic year 2017/2018. The research subjects were 31 students in total. The research result shows that the learning outcome of two-dimensional figure circumference and wide of the grade IV D students can be developed very well. It is shown by the average test result of 83.87% where the students who reach the minimum mastery criteria after touch media is used in order to to improve student learning outcomes.